Evaluación de la influencia de la materia prima, el tiempo de tostión y el grado de molienda sobre el rendimiento del proceso de extracción para la producción de café soluble (2019)
A three-factor experiment design was executed, which were called “coffee”, “roasting” and “grinding” with six levels of the first, corresponding to six green coffee samples with different grain sizes obtained from the threshing plant Racafé in Bogotá, the samples were roasted on three levels (light, medium, dark) and ground on three different levels (fine, medium, thick) according to the guidelines of NTC 2441, which resulted in a total of 54 treatments The response variable was the extraction performance obtained with five repetitions and calculated according to bibliographic references previously validated with the methodology established in NTC 4602-1, the variable “global impression”, corresponding to the sensory quality, was also determined for each treatment of the sample, obtained by evaluation in Racafé cupping panel. The data were analyzed using the ANOVA variance analysis and the Tukey means comparisons method, using the Minitab 18 statistical software. The best treatments were selected by multicriteria evaluation and these were compared with the current yield of commercial coffees. Finally, the variation in the operating costs of the industrial process for the production of soluble coffee for the selected treatments was analyzed.